Integrasi Soft Skills dan Hard Skills sebagai Kunci Efektivitas Pendidikan Vokasi di Era Transformasi Digital - Ninin Nurhidayati; Risna Amelia (SECAD, 2025)
Digital transformation has significantly altered job structures and workforce competency demands. The professional world no longer solely requires workers with high technical skills but also individuals equipped with communication, adaptability, teamwork, and problem-solving abilities. Vocational education, as a pathway directed toward job readiness, faces challenges in adjusting its curriculum to align with these evolving requirements. This study aims to analyze the effectiveness of integrating soft skills and hard skills on the outcomes of vocational education graduates in the digital transformation era. Employing a descriptive quantitative approach based on secondary data and simulations, the research develops the Work Effectiveness Index (Indeks Efektivitas Kerja/IEK) as a measurement model. Data were sourced from labor market competency reports and previous studies. The simulation results indicate that graduates with integrated competencies possess higher work effectiveness levels compared to those with solely technical orientation. These findings affirm that the integration of soft skills and hard skills is a key strategy in enhancing the relevance and effectiveness of vocational education in the digital transformation era